DAMPAK MEDIA SOSIAL WHATSAPP TERHADAP PRESTASI BELAJAR PRAKARYA KEWIRAUSHAAN DI SMK MANDIRI 02 BALARAJA (Studi Pada Program Pendidikan Ekonomi FKIP UNIS Tangerang) - muhamad bili fatullah; heni cahya ramdani (Journal of Business Education and Social, 2020)
The purpose of this study is to study whether or not the use of WhatsApp social media on entrepreneurship learning achievement in SMK Mandiri 02 Balaraja. This study uses a quasi-experimental method with a nonequivalent design. The sample consisted of an experimental class of 37 students and a control class of 32 students and the technique of combining data using test instruments, student learning behaviors, teacher teaching behaviors and questionnaires. The form of the test consists of 5 questions and the instrument test has been done. The results showed that there was no significant influence in the use of WhatsApp social media on learning achievement of entrepreneurial craftsmanship, while the results of students' perceptions of WhatsApp learning media through questionnaires could be concluded as "good" results, the lowest scoring results were 55 and the highest total score was 75 and in the control class had the lowest total score of 50 the highest score of 65, and the results of the teaching behavior assessment of teachers showed a total score of 69 so that it could be related to the results of the criteria being "sufficient".